ION-EXCHANGE MEMBRANE CHROMATOGRAPHY AS AN ALTERNATIVE METHOD OF SEPARATION OF POTATO Y VIRUS - Treder, Krzysztof; Zacharzewska, Bogumiła; Przewodowska, Agnieszka; Przewodowski, Włodzimierz; Otulak, Katarzyna (Plant Breeding and Seed Science, 2015)
Procedures of separation of virus particles from a plant material are multistage. Furthermore often they are difficult in terms of methodology and require use of expensive, highly specialist equipment and yield of separation is often low. The antigen obtained is often degraded and contains admixtures of other proteins. Therefore, generation of high quality and specificity antibodies based on such antigen is very difficult and quality of the antibodies has impact on reliability, sensitivity and unambiguity of results of immunodiagnostic tests (e.g. ELISA) that are currently conventionally used to detect vegetable viruses. In this study three conventionallyperformed methods of separation of potato virus Y (PVY) were compared and a method of separation based on membrane chromatography, as an alternative separation technique, has been presented. It has been demonstrated that in proper process conditions good quality virus preparation can be obtained.